The Long Road to Palestinian Reform - Barsalou, Judy (Middle East policy, 2003)
Although Palestinian political reform lately has become the subject of intense discussion in Washington, the subject is hardly a new one. Barsalou discusses who is calling for Palestinian reform and why, what kinds of reforms are contemplated and what has been accomplished to date, and the major obstacles to reform.